The effect of simulation education on quality of the spinal column fixation - Fateme Moghimi (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: Nursing in crisis consists of pre hospital specialized skills and cares for the survival of the injured, the lowering of physical and mental damage, safely transferring of injured and preventing of complication and worsening of their damages. Lack of nurse’s skills may ne lead to problems aggravation and irreversible complications. Therefore, Obtaining Skill and experience in actual situations gradually is not enough rather, nurses should be educated step by step. Simulation in workshop is one of the best education ways. The purpose of this research is to investigate the effect of simulation education on quality of the spinal column fixation of simulated patient by nursing student of Kashan 1395.